2006
DOI: 10.1002/ajhb.20510
|View full text |Cite
|
Sign up to set email alerts
|

Growth rates and life histories in twenty‐two small‐scale societies

Abstract: This study investigates variation in body growth (cross-sectional height and weight velocity) among a sample of 22 small-scale societies. Considerable variation in growth exists among hunter-gatherers that overlaps heavily with growth trajectories present in groups focusing more on horticulture. Intergroup variation tends to track environmental conditions, with societies under more favorable conditions displaying faster growth and earlier puberty. In addition, faster/earlier development in females is correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
398
5
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(432 citation statements)
references
References 59 publications
24
398
5
5
Order By: Relevance
“…Some studies include samples covering the whole lifespan. However, in this study, we only considered samples above 20 years of age, which corresponds to the age at first reproduction in human societies (Walker et al, 2006). Previous human brain aging studies using transcriptome data have also suggested gene expression patterns before and after the age of 20 are discontinuous (Colantuoni et al, 2011; Dönertaş et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies include samples covering the whole lifespan. However, in this study, we only considered samples above 20 years of age, which corresponds to the age at first reproduction in human societies (Walker et al, 2006). Previous human brain aging studies using transcriptome data have also suggested gene expression patterns before and after the age of 20 are discontinuous (Colantuoni et al, 2011; Dönertaş et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…1 Previous studies have shown that the divergence between ancestral pygmy populations and ancestral non-pygmy populations is quite ancient and occurred around 60 000 years ago. 2,3 Many evolutionary hypotheses have been proposed to explain this phenotype, 4 which could be due to an adaptation to food scarcity, 5 to the hot and humid climate of the rainforest, 6 to the density of this environment where mobility is uneasy, 7 to a life-history tradeoff in a context of high mortality 8,9 or to particular mate choices. 10 However, none of these hypotheses has proven to be true 4,11 and the evolution of the short stature of African pygmies remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…LH strategies also vary within species, and individual differences in LH variables such as reproductive timing and senescence (Walker et al 2006;Ellis et al 2012) may be driven by exposure during early life to cues to extrinsic mortality risk (Wilson and Daly 1997;Ellis et al 2012). Because high extrinsic mortality risk favors current reproduction over future reproduction, mortality risk may promote earlier puberty and thus earlier age at first copulation (Lam et al 2002;Walker et al 2006;Friedlander et al 2007).…”
Section: Introductionmentioning
confidence: 99%